In-situ polymerization of eco-friendly waterborne polyurethane/polydopamine-coated graphene oxide composites towards enhanced mechanical properties and UV resistance. (1st November 2022) - Xu, Wenqing; Lv, Yadong; Kong, Miqiu; Huang, Yajiang; Yang, Qi; Li, Guangxian
Abstract: Waterborne polyurethane (WPU) has attracted significant attention recently, considering its advantages of sustainability and low toxicity. However, fabricating WPU with excellent initial performance as well as extraordinary long-term stability is extremely challenging. In this study, we demonstrated the potential of polydopamine-modified graphene oxide (DGO) in the preparation of strong, tough, and highly durable WPU materials via in-situ polymerization. With the addition of only 2.0 wt% DGO, the tensile strength, and Young's modulus of WPU increased from 17.6 ± 2.6 to 56.5 ± 3.1 MPa (by 221%) and from 8.5 ± 1.1 MPa to 22.0 ± 0.8 MPa (by 159%), respectively. Compared with WPU, the degree of surface oxidation of the UV-aged WPU/DGO composites was substantially reduced from 174.3 to 19.5 (by 88% at maximum). Based on the cross-sectional analysis, the oxidation depth of the WPU/DGO composites was significantly reduced from 11.25 μm to 3.75 μm (by 66%). These improved properties originated not only from stronger interactions between DGO and WPU via the interfacial PDA layers and better dispersion of DGO, but also from the unique ultraviolet light absorption ability and free radical trapping ability of DGO. This facile yet environment-friendly in-situ synthesis technique is eco-sustainable and expected to promote the commercial availability of high-quality WPU and conserve natural resources. Graphical abstract: Image 1 Highlights: WPU/DGO composites were synthesized successfully via in-situ polymerization. PDA layer enhanced the UV absorption and free radical scavenging ability of GO. Covalent bonding through urea groups between DGO and WPU matrix was verified. Tensile strength and Young's modulus of WPU/DGO composites were simultaneously boosted. Surface oxidation and oxidation depth of WPU/DGO were significantly suppressed.